Ethical Awareness Scale: Replication Testing, Invariance Analysis, and Implications. Issue 4 (2nd October 2019) - Milliken, Aimee; Ludlow, Larry; Grace, Pamela
Abstract: Background: Ethical awareness (EA) enables nurses to recognize the ethical implications of all practice actions and is an important component of safe and quality nursing care. Evidence suggests that nurses may sometimes feel underprepared to recognize and address ethical issues as they arise in practice. The Ethical Awareness Scale (EAS) presented strong evidence as a psychometrically sound measure of EA in critical care nurses in pilot testing. The present study extends earlier work by (a) expanding the sample, (b) replicating the psychometric analyses, (c) more deeply investigating data-to-model fit, and (d) providing guidelines for the interpretation of EAS scores and subsequent practice-focused and educational interventions.Methods: This study utilized two sets of cross-sectional EAS survey results with ICU nurse respondents from two hospitals in New England. Invariance testing using simple OLS regression was conducted between the item estimates of both samples. The final Rasch analysis utilized a rating scale model. Finally, a score interpretation framework was developed.Results: 240 participants were included in the combined analysis. Nurses were predominantly female (93.1%), aged 25-35 (39.9%), and Bachelor's degree prepared (73.4%). Mean levels of EA were in the low/moderate range (M = 36.2/54). Cronbach's alpha of 0.86 was achieved. The Rasch analysis demonstrated a variable map structure consistent with the hypothesized item order, scoring categories that were sufficiently used by respondents, and adequate model-data fit.Conclusions: This study demonstrates that the EAS is a psychometrically sound and meaningful measure of EA in critical care nurses with item difficulty estimates that are invariant across samples. A raw score on the EAS can be practically interpreted, given the theoretical description of what a nurse at each level of the scale's continuum may "look" like in terms of EA using the diagnostic interpretation table. These findings have implications for nursing education and practice.